1996
DOI: 10.1016/0165-3806(95)00214-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of divergence in dopamine responsiveness in genetically selected rat lines is preceded by changes in pituitary-adrenal activity

Abstract: A b s tra c tTwo pharmacogenetically selected Wistar rat lines have been used as a model for individual variability in behavioral and neuroendocrine responses. As a selection criterion the behavioral responsiveness For the dopamine agonist apomorphine was used, giving rise to the apomorphine-susceptible (apo-sus) and apomorphine-unsuseeptible (apo-unsus) rat lines. This selection has been maintained over 16 generations. Recent studies have shown that adult rats of these selection lines also show pronounced dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Furthermore, it was shown that corticosteroids via GRs may play an important role in the sensitization of the DA system [37]. Interestingly, the development of divergence in DA responsiveness in apomorphine susceptible and unsusceptible rat lines, that also differ in coping strategy, is preceded by changes in pituitary -adrenal activity [38].…”
Section: Interaction Of Corticosteroids With Da and 5-ht Pathways Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was shown that corticosteroids via GRs may play an important role in the sensitization of the DA system [37]. Interestingly, the development of divergence in DA responsiveness in apomorphine susceptible and unsusceptible rat lines, that also differ in coping strategy, is preceded by changes in pituitary -adrenal activity [38].…”
Section: Interaction Of Corticosteroids With Da and 5-ht Pathways Andmentioning
confidence: 99%
“…Consequently, corticosteroids may alter neural transmission in the serotonergic (5-hydroxytryptamine, 5-HT) [35] and dopaminergic (DA) system [32]. Indirectly, it has been shown that 5-HT as well as DA neurotransmission is altered in adult proactive individuals compared to adult reactive individuals [27,38].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in the introduction, the APO-SUS rats are characterized by higher levels of TH immunoreactivity in the ventral striatum (Van der Elst et al, in press a), a higher amount of dopaminergic D2 receptors in the striatum (Rots et al, 1996), a functionally lower noradrenergic activity in the ventral striatum (Ellenbroek and Cools, 1993;Cools et al, 1990), and lower free plasma levels of corticosterone (Rots et al, 1995) than the APO-UNSUS rats. All these features are associated with less alcohol consumption (Stefanini et al, 1992;Gongwer et al, 1989;Gongwer et al, 1989;Murphy et al, 1982;Casu et al, 2002;Mcbride and Li, 1998;Taylor et al, 1990;Murphy et al, 1987), and this study therefore gives more weight to this correlation.…”
Section: Discussionmentioning
confidence: 96%
“…The differential response of the APO-SUS and the APO-UNSUS rats to the acute challenge can be attributed to the interline differences in the reactivity of their HPA axis. APO-SUS rats are marked by a higher and prolonged stress-induced response of the HPA-axis, as measured by the release of ACTH and corticosterone (Rots et al, 1996;Cools et al, 1990), which might explain why the relatively stress-sensitive APO-SUS rats have a strong and long-term increase in alcohol consumption after the acute challenge, whilst the stressinsensitive APO-UNSUS rats have a small and short-term increase in intake. Alternatively, the noradrenergic activity of the ventral striatum might also be involved in the stress-induced change in consumption.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation